CRIMINAL RESPONSIBILITY OF INDONESIAN NATIONAL ARMED FORCES MEMBERS IN CYBER CRIME - Fera Kusumawati; Supri Abu; Diding Rahmat (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
The development of digital technology and the expansion of cyberspace have presented stra-tegic opportunities for the nation, but have also opened up the potential for new and increas-ingly complex crimes, including cybercrimes involving members of the Indonesian National Armed Forces (TNI). As part of the national defense apparatus, TNI soldiers are subject to the national legal system when committing electronic-based unlawful acts. This study aims to examine the legal provisions for cybercrimes in the laws and regulations applicable to TNI members and to analyze the forms of criminal liability for soldiers committing digital crimes. The method used is normative juridical research with a statute approach and a case approach through a review of relevant laws and regulations, legal doctrines, and court decisions. The results of the study indicate that the regulation of cybercrime for TNI members is basically based on the ITE Law (Law 11/2008 jo. Law 19/2016 jo. Law 1/2024), the New Criminal Code (Law 1/2023), the Criminal Code, the Military Court Law 31/1997, and the Military Discipline Law 25/2014. However, until now there has been no norm that specifically regulates cyber-military offenses so that the potential for overlapping jurisdictions is still found, especially in the application of lex specialis KUHPM and lex generalis ITE Law. Forms of criminal liability for TNI members include individual liability, command liability, and disciplinary liability if the act does not fulfill the elements of a crime. The phenomenon of spreading hoaxes by soldiers and involvement in online gambling shows that the handling of cyber violations is still dominated by disciplinary sanctions, not criminalization. This study concludes that the lack of cyber norms within the military legal framework requires more comprehensive regulatory reform, including revising the Criminal Code (KUHPPM), aligning the ITE Law with the military justice system, and developing technical guidelines for digital evidence for soldiers involved in cybercrimes. Strengthening digital literacy, establishing data security SOPs, and clarifying jurisdictional boundaries are necessary to ensure law enforcement is fair, consistent, and in line with the principles of TNI professionalism.